2007 IEEE 20th International Conference on Micro Electro Mechanical Systems (MEMS) 2007
DOI: 10.1109/memsys.2007.4433046
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum microfabrication on live fruit fly

Abstract: The survival rate of Drosophila when exposed to moderate vacuum levels is studied and it is established that the organism can be subjected to 55 mTorr vacuum for periods as long as 70 minutes with a significant rate of survival (>20%). This finding opens a number of new opportunities for performing fabrication processes, similar to the ones performed on a silicon wafer, on a fruit fly as a live substrate. As a model microfabrication process, it is shown how a collection of Drosophila can be made to self-assemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…However we use commercially available parts which allows for easy scaling of the electronics fabrication and our process for gluing the electronics to the insects is similar to the process for attaching tracking markers to bees in commercial hives. Additionally, researchers have also shown that insects can survive common microfabrication processes such as deposition of conductive material in a vacuum chamber [68,69] and performing surgeries at different stages of an insect's life cycle. This suggests potential approaches for mass attachment of electronics or fabricating devices on insects themselves.…”
Section: Discussionmentioning
confidence: 99%
“…However we use commercially available parts which allows for easy scaling of the electronics fabrication and our process for gluing the electronics to the insects is similar to the process for attaching tracking markers to bees in commercial hives. Additionally, researchers have also shown that insects can survive common microfabrication processes such as deposition of conductive material in a vacuum chamber [68,69] and performing surgeries at different stages of an insect's life cycle. This suggests potential approaches for mass attachment of electronics or fabricating devices on insects themselves.…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that more than half of fruit flies can tolerate a vacuum of 55 mTorr for 60 min [8]. A segment of dorsal vessel tissue of a cockroach embryo continued to contract for more than 260 days in culture medium [9].…”
Section: Introductionmentioning
confidence: 92%
“…When kept at 55 mTorr pressure for 60 min more than half of the flies survived. 13 As another example, a segment of dorsal vessel (DV) tissue of a cockroach embryo continued to contract for more than 260 days in culture medium. 14 Due to their robustness not only at an individual level but also at a tissue level, insects could be useful as a biological part of a hybrid robot system.…”
Section: Introductionmentioning
confidence: 99%